2010
DOI: 10.1002/ar.21277
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Dorsal Circumorbital Bones in the Leopard Gecko (Eublepharis macularius) and Its Bearing on the Homology of These Elements in the Gekkota

Abstract: Five nominal elements comprise the circumorbital series of bones in gekkotans: prefrontal, postfrontal, postorbital, jugal, and lacrimal. Determination of the homology of two of these, the postfrontal and postorbital, has been particularly problematic. Two conflicting hypothesis exist relating to these: either the postorbital is lost and the postfrontal remains or they fuse during development to form a combined element, the postorbitofrontal. Such a combined element apparently occurs in at least some members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…These two clades present a reduced jugal bone and only one bone in the posterodorsal edge of the eye socket, termed the postorbitofrontal. For an alternative interpretation of this bone in the Gekkota see Wise and Russell (2010).…”
Section: Character Variation and Distributionmentioning
confidence: 99%
“…These two clades present a reduced jugal bone and only one bone in the posterodorsal edge of the eye socket, termed the postorbitofrontal. For an alternative interpretation of this bone in the Gekkota see Wise and Russell (2010).…”
Section: Character Variation and Distributionmentioning
confidence: 99%
“…In squamates, usually the bone that participates in the postorbital bar and the upper temporal bar is the postorbital, while the postfrontal usually clasps the frontoparietal suture (Evans, ). Developmental data for gekkotans have shown that in Eublepharis macularius , the postorbitofrontal corresponds only to the postfrontal, but this interpretation is conditioned to an anterior shift of the postorbital to a parafrontal position and its successive fusion with the frontal bone (Wise and Russell, ). In Calyptommatus , the postorbitofrontal is indeed formed by the fusion of a well‐developed postorbital and reduced postfrontal (Roscito and Rodrigues, ).…”
Section: Discussionmentioning
confidence: 99%
“…They also gave some consideration to dermal skull development in geckos, and this was also examined by Brock (1932: Lygodactylus , Pachydactylus ), El‐Toubi and Kamal, 1961a,b,c: Ptyodactylus ), Rieppel, 1992: Cyrtodactylus ), Wise et al . (2009, Eublepharis ), and Wise and Russell, 2010: circumorbital bones). However, to date, there has been no detailed description of pre‐hatching dermatocranial development in a gekkotan, based on a full embryonic staging series.…”
Section: Introductionmentioning
confidence: 99%